Experimental study of effectiveness of local application of electroneurostimulation, cortexin and methylprednisolone in acute spinal cord injury. - Tsymbaliuk, V. I.; Dzyak, L. A.; Sal’kov, N. N.; Rodinsky, A. G.; Tkachenko, S. S. (Medicni Perspektivi, 2014)
The tasks were to investigate the effect of topical electroneurostimulation, cortexin and methylprednisolone in acute spinal cord injury in electrophysiological experiments on laboratory rats. The animals underwent half transection of the spinal cord in the lower-thoracic area to simulate Brown-Sequard’s syndrome. Drugs were administered subdurally once daily in the dose of 0.03 mg for cortexin and 0.7 mg for methylprednisolone during 72 hours. Electrophysiological studies were carried out using standard electrophysiological apparatus. Reliable changes of bioelectric indicators in neuromuscular complex during topical application of electrical stimulation, as well as in administered methylprednisolone, failed to be found. However, local application of cortexin in terms of traumatic spinal cord injury due the antioxidant and neurotrophic effect results in improvement of bioelectrical indicators; this is manifested in reliable (p<0.05) increase of amplitude of the background electromyogram impulses at rest by 33% and increase of spontaneous oscillations frequency by 29.82%.